Radiocarbon ages of sediment core IDLE-MAT10-2B from Lake Matano in Sulawesi, Indonesia - Parish, Meredith; Russell, James M; Konecky, Bronwen; Du, Xiaojing; He, Chengfei; Bijaksana, Satria; Vogel, Hendrik (PANGAEA, 2024)
We produced an age model based on radiocarbon dates measured in the 8-m composite Lake Matano sediment core that spans the last deglaciation. There are 11 radiocarbon ages in the 8 m core.
Keywords: alkanes; Carbon; deglacial; Deglaciation; hydroclimate; hydrogen; Indonesia; Indo-Pacific Warm Pool; Last Glacial Maximum; Leaf wax; LGM; Maritime Continent; precipitation; Warm Pool